2011
DOI: 10.1038/bmt.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bimonthly extracorporeal photopheresis in refractory chronic mucocutaneous GVHD

Abstract: Extracorporeal photopheresis (ECP) has become a recognised treatment for steroid-refractory chronic GVHD (cGVHD), but the optimal frequency and duration of treatment are yet to be established. We report on 82 consecutive patients with mucocutaneous cGVHD who received a bimonthly regimen of ECP treatment for two consecutive days, which could be subsequently tapered to a monthly regimen depending on response. Patients were steroid-refractory, steroid-dependent or steroid-intolerant, and 29 (35%) had multiorgan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 29 publications
4
51
1
2
Order By: Relevance
“…The results are remarkably consistent with the retrospective study we have reported previously. 2 The earlier study showed that 77% of patients who completed 6 months of ECP treatment had a reduction in immunosuppression, and the prospective study showed that 80% of patients who completed 6 months of ECP had a reduction in immunosuppression. One limitation of this study was the number of patients who did not complete 6 months of treatment (11/38, 29% of patients).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are remarkably consistent with the retrospective study we have reported previously. 2 The earlier study showed that 77% of patients who completed 6 months of ECP treatment had a reduction in immunosuppression, and the prospective study showed that 80% of patients who completed 6 months of ECP had a reduction in immunosuppression. One limitation of this study was the number of patients who did not complete 6 months of treatment (11/38, 29% of patients).…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have previously reported the efficacy of ECP in the management of cGVHD in retrospective studies. [2][3][4][5] To date, there are only a few prospective studies of ECP for this condition [6][7][8][9] and one randomised prospective trial. 10 In addition, there are few data on the effect of ECP on quality of life (QoL) in patients with cGVHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other retrospective studies have shown benefit of ECP in treatment of cGVHD as well [106,128]. A study of 80 patients receiving two consecutive ECP treatments every 2 weeks showed that 84 % patients were able to complete 6 months of treatment and 50 % patients had reduction in symptoms [129], thus suggesting this probably is an effective regimen. Some biomarkers were proposed which may predict the response to ECP.…”
Section: Extracorporeal Photopheresis (Ecp) and Puvamentioning
confidence: 99%
“…6 ECP is effective in the treatment of both steroid-refractory and -dependent aGVHD and cGVHD. [7][8][9][10][11][12] Here, we report a retrospective analysis of 62 patients with aGVHD and cGVHD treated with ECP employing the COBE Spectra System. The aim was to assess possible factors influencing response to ECP and survival such as patients' clinical features, concomitant immunosuppressive treatment, and GVHD characteristics.…”
Section: Introductionmentioning
confidence: 99%